The Constraints of the Arabic Subtitled Film - Al Droubi, Sandrella (2004)
A Master of Arts Thesis Submitted to the Department of English & Translation Studies by Sandrella Al Droubi Titled, "The Constraints of the Arabic Subtitled Film," June 26, 2004. Advisor Dr. Basil Hatim. Thesis available only in hard copy in Reference and AUS Archives